2010
DOI: 10.1166/jnn.2010.1736
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of CdSe/ZnS Quantum Dots Encapsulated in Poly(ethylene glycol)-<I>b</I>-Poly(D,L-lactide) Micelle Nanoparticles

Abstract: The final goal of this study is to develop multi-functional organic/inorganic hybrid nanoparticles, which can be utilized as biomedical imaging probes and drug delivery carriers. As an initial step toward this goal, we encapsulated CdSe/ZnS quantum dots (QDs) into poly(ethylene glycol)-b-poly(D,L-lactide) (PEG-PLA) micelles using a solid dispersion method. The size and fluorescent intensity of QDs encapsulated in PEG-PLA micelles depended on the amount of incorporated QDs. For example, when the amount of QDs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our results suggest that the positive charge of the QDs counterbalanced the negative charge of the PLGA nanospheres, and the magnitude of the positive charge of QDs loaded in PLGA nanospheres was affected by the amount of the encapsulated QDs. Lee et al also reported the zeta-potential of micelles was changed to the positive charged surface after loading QDs [24]. The surface characteristics of nanoparticles are an important factor determining their life span and fate during circulation relating to their capture by macrophages [25].…”
Section: Nir Qds-loaded Plga Nanospheresmentioning
confidence: 99%
“…Our results suggest that the positive charge of the QDs counterbalanced the negative charge of the PLGA nanospheres, and the magnitude of the positive charge of QDs loaded in PLGA nanospheres was affected by the amount of the encapsulated QDs. Lee et al also reported the zeta-potential of micelles was changed to the positive charged surface after loading QDs [24]. The surface characteristics of nanoparticles are an important factor determining their life span and fate during circulation relating to their capture by macrophages [25].…”
Section: Nir Qds-loaded Plga Nanospheresmentioning
confidence: 99%
“… 6 9 Among the different imaging modalities investigated, fluorescence-based techniques, despite their intrinsic limitations such as tissue self-fluorescence and poor tissue penetration at shorter wavelength, present a major advantage over their competitors as they do not require the use of radioactive labels (nuclear imaging), rare elements such as lanthanides (magnetic resonance imaging), or large local concentrations of heavy elements (computed tomography). The synthesis of fluorescent polymer nanoparticles relies mostly on three distinct strategies: 1, the chemical conjugation of organic dyes 10 , 11 to amphiphilic polymers; 2, the encapsulation of organic dyes, 12 quantum dots (QD) 13 or fluorescent polymers 14 into the hydrophobic core of micelles; and 3, the synthesis of fluorescent amphiphilic polymers either by copolymerizing fluorescent monomers with a hydrophilic comonomer to generate brush architectures, 15 19 or through postpolymerization functionalization of a hydrophobic fluorescent polymer with a reactive hydrophilic polymer. 19 , 20 Each approach presents drawbacks, such as the unknown and often limited efficiency of dye conjugation reactions and tedious purification of the conjugates for the first strategy.…”
mentioning
confidence: 99%